PULMONARY ARTERY DIAMETER ON CHEST CT PREDICTS IN-HOSPITAL MORTALITY IN PATIENTS WITH COVID-19 PNEUMONIA - Baytugan, Nart Zafer; Celik, Aziz Inan; Bezgin, Tahir (Sanamed, 2022)
Background: Enlargement of the pulmonary artery (PA) could be helpful in risk stratification by the chest CT on the admission of COVID-19 patients. Methods: This study aimed to associate PA diameter and overall mortality in COVID-19 pneumonia. We designed a retrospective study between January 2021 and May 2021 in tertiary-level hospitals in Gebze, Turkey. Subjects were evaluated in two groups according to their survivor status (survivors and non-survivors). Then biochemical, demographic, and clinical values were compared via the groups to define the predictive value of PA diameter on chest CT images. Results: In the enrolled 594 COVID-19 in-hospital patients (median age was 45 (34-58) years, 263patients (44.3%) were female. 44 patients (7.4%) died during hospitalization. Multivariate Cox-proportion regression model yielded main PA ≥ 29 mm on admission showed that as independent predictors of death (long rank <0.001, median survival time 28 days). Cumulative survival rates were MPAD ≥ 29 mm 45% and < 29 mm 90% yielded (p < 0.001) Conclusions: PA dilatation is strongly linked with in-hospital mortality in hospitalized patients with COVID-19 infection. Thus increased PA diameter on chest CT at admission may guide rapid and early diagnosis of high-risk patients.